Improved Fischer esterification of substituted benzoic acid under sealed-vessel microwave condition - Abd Hamid, Shafida; Hamzah, Nurasyikin; Abdul Rahim, Aisyah Saad (Penerbit Universiti Sains Malaysia, 2015)
Ethyl-4-fluoro-3-nitro benzoate was synthesised in good yield under closed vessel conditions using a single-mode microwave. This simple method involved adding catalytic amounts of H2SO4 at specific intervals of time to overcome the problems associated with equilibrium. The method was first optimised in terms of temperature, and the effect of using various solvents on the ester product was also investigated. Primary alcohols produced the highest yield of the ester product compared to secondary alcohols, and tertiary alcohol resulted in the lowest.